IMPROVEMENT OF GOGO RICE SEEDS THROUGH ADAPTIVE LOCATIONS AND STORAGE - Mustakim Mustakim; Sakka Samudin; Maemunah Maemunah; Adrianton Adrianton; Yusran Yusran (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Production and management technologies are needed to produce great seeds. This study aims to obtain the location and length of time to store upland rice seeds. The study was conducted in Tamarenja and Kalukubula villages. Germination testing was carried out at the Seed Science and Technology Laboratory of the Faculty of Agriculture from May to December 2019. The seeds used were newly harvested seeds from the field. The treatment used a randomized two-factor block design. The first factor was storage locations: indoor Tamarenja, outdoor Tamarenja, indoor Kalukubula and outdoor Tamarenja. The second factor consisted of two storage times, namely: one month and two months. The treatments repeated six times, so there were 48 experimental units where each experimental unit contains 50 seeds, and the whole seeds used were 2,400. Data analysis used Fisher's test and continued with 1% Tukey’s HSD test. The results showed that the best storage location was in Kalukubula, both outdoors and indoors. The best storage time was two months. Those produced the highest germination capacity and growth potential and faster germination time, percentage of moldy seeds, and moldy sprouts.